Innate immune defects in HIV permissive cell lines. Issue 1 (December 2016) - Rausell, Antonio; Muñoz, Miguel; Martinez, Raquel; Roger, Thierry; Telenti, Amalio; Ciuffi, Angela
Abstract Background Primary CD4+ T cells and cell lines differ in their permissiveness to HIV infection. Impaired innate immunity may contribute to this different phenotype. Findings We used transcriptome profiling of 1503 innate immunity genes in primary CD4+ T cells and permissive cell lines. Two clusters of differentially expressed genes were identified: a set of 249 genes that were highly expressed in primary cells and minimally expressed in cell lines and a set of 110 genes with the opposite pattern. Specific to HIV, HEK293T, Jurkat, SupT1 and CEM cell lines displayed unique patterns of downregulation of genes involved in viral sensing and restriction. Activation of primary CD4+ T cells resulted in reversal of the pattern of expression of those sets of innate immunity genes. Functional analysis of prototypical innate immunity pathways of permissive cell lines confirmed impaired responses identified in transcriptome analyses. Conclusion Integrity of innate immunity genes and pathways needs to be considered in designing gain/loss functional genomic screens of viral infection.